Genetic Diversity of Small, Isolated and Fragmented Blackbuck (Antilope cervicapra, L.) Populations of Haryana based on mtDNA Barcoding - Delu, Vikram; Singh, Dharmbir; Batra, Kanisht; Maan, Sushila; Saini, Deepesh (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Mitochondrial DNA (mtDNA) analysis is a valuable tool in forensic for species identification because mtDNA is maternally inherited, and  there are often many copies of mtDNA in a cell. This makes it possible to obtain DNA from degraded or small samples, such as those  found in forensic investigations. Additionally, mtDNA analysis can provide information on the evolutionary relationships among different  populations and species. In the present study, mtDNA analysis was employed to examine the genetic diversity and phylogenetics of small  Blackbuck populations in Haryana, India. The six tissue and eleven fecal samples were collected and amplified with the cytochrome c  oxidase subunit I gene. Various statistical approaches were used to examine the parameters like Genetic p-distance, Genetic diversity,  Tajima’s D, Fu’s Fs Test, Mismatch distribution graphs. The overall value of π = 0.013 and Hd = 0.65 of all selected populations suggested  that the population of Blackbuck under investigation may have an equilibrium stage. The findings of present investigation provide insight  into the genetic diversity and highlight the importance of maintaining connectivity among fragmented populations. This information  is crucial for designing effective conservation strategies, as well as for addressing issues associated with species identification and  combating wildlife-related crimes.
Keywords: Blackbuck; Cytochrome c; Mitochondrial DNA; Wildlife Forensic